Idiopathic portal hypertension (perisinusoidal fibrosis) after renal transplantation. Issue 6 (June 1979) - Nataf, C; Feldmann, G; Lebrec, D; Degott, C; Descamps, J M; Rueff, B; Benhamou, J P
Abstract : We report the cases of two renal transplant recipients suffering from idopathic portal hypertension, a condition characterised by increased portal venous pressure in the absence of both histological lesion of the liver and obstruction of the portal vein. In these two patients, perisnusoidal fibrosis, invisible by light microscopy, was demonstrated by electron microscopy; it is suggested that partial obstruction of hepatic sinusoids by perisinusoidal fibrosis could be the mechanism for increased portal venous pressure in all the patients with idiopathic portal hypertension. In these two patients, who received 6-mercaptopurine and azathioprine, perisinusoidal fibrosis might be the consequence of prolonged administration of these drugs.